Odpowiedzi

2009-12-22T16:37:52+01:00
6x+5y-7y-6+10x=0
16x-2y-6=0
y=(16x-6):2
y=8x-3

5x+4y+9+5x+25-8y=0
10x-4y+34=0
10x-4(8x-3)+34=0
10x-32x+12+34=0
-22x+46=0
x=2,09

y=8*2,09-3
y=1,18
Najlepsza Odpowiedź!
2009-12-22T16:39:15+01:00
6x+5y=7y+6+10x
5x+4y+9=-5x-25+8y

6x-10x+5y-7y=6
5x+5x+4y-8y=-25-9

-4x - 2y =6 /*(-2)
10x -4y = -34

8x +4y = -12
10x -4y = -34

dodaję równania stronami i redukuje mi się y

18x = - 46 /:18
x = -46/18

Podstawiam do pierwszego równania:
-4*(-46/18) - 2y =6
92/9 - 2y = 6
2y = -6 + 92/9
2y = -6 + 10całych 2/9
2y = 4 całe 2/9 /:2
y = 38/9 : 2
y = 38/9 * 1/2
y = 19/9
y=2 całe 1/9

Odp. x = -2 całe5/9
y = 2 całe 1/9
2009-12-22T16:41:03+01:00
6x+5y=7y+6+10x
5x+4y+9=-5x-25+8y
6x - 10x + 5y - 7y = 6
5x + 5x + 4y - 8y = - 25 - 9
- 4x - 2y = 6 mnożymy przez - 2
10x - 4y = - 34
8x + 4y = - 12
10x - 4y = - 34
dodajemy stronami
8x + 10x + 4y - 4y = - 34 - 12
18x = - 46
x = - 46/18 = - 23/9 = - 2 i 5/9
10x - 4y = - 34
- 230/10 - 4y = - 34
- 230 - 40y = - 340
- 40y = - 340 + 230
- 40y = - 110
y = 110/40 = 11/4 = 2,75 a x = - 2 i 5/9